Students’ Perceptions Toward the Use of TikTok as a Digital Learning Tool in Learning English Vocabulary At SMAN 1 Loa Janan - Muhammad Zaidan Adi Putra; Ade Ismail Ramadhan Hamid; Rani Herning Puspita (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to investigate students' perceptions toward the use of TikTok as a digital learning tool in learning English vocabulary at SMAN 1 Loa Janan. The background of this study is based on the challenges students face in mastering English vocabulary despite years of formal instruction. In the digital era, TikTok has emerged as a popular social media platform among students and shows potential as an educational tool. However, students' perceptions toward using TikTok for vocabulary learning have not been clearly identified, particularly in Indonesian senior high schools. This study uses a quantitative descriptive research design with a questionnaire as the primary data collection instrument. There were 32 students from class X-3 participating in the study. Data collection was conducted through a Likert-scale questionnaire consisting of 15 items measuring students' perceptions across four dimensions: perceived usefulness, perceived ease of use, learning interest, and learning engagement. The results showed that the questionnaire was valid (Corrected Item-Total Correlation values ranging from 0.756 to 0.867, all exceeding 0.30) and highly reliable (Cronbach's Alpha = 0.970). Descriptive statistical analysis revealed a mean perception score of 49.69 (SD = 14.16), which falls within the moderate perception category. The scores ranged from 19 to 75, indicating considerable variability in students' perceptions. Thus, students generally hold moderately positive perceptions toward TikTok as a digital learning tool for vocabulary learning, though significant individual differences exist. These findings provide valuable insights for educators seeking to integrate social media platforms into language teaching practices.